IMPLEMENTATION OF THE CAR WASH INDEPENDENCE DEVELOPMENT PROGRAM IN AN EFFORT TO FULFILL THE RIGHTS OF INMATES IN THE CORRECTIONAL INSTITUTION - Irsyaad, Rizky Muhammad (Universitas Nusa Cendana, 2025)
The purpose of this article is to understand the importance of the independence development program as an effort to fulfill the rights of prisoners while serving their criminal term in a correctional institution. Fulfilling the rights of prisoners is an effort to uphold the human rights that humans have. This research examines previous research on the subject and available literature using qualitative research methods with a literature review strategy. The results show a number of difficulties in implementing self-sufficiency programs, including inadequate funding, poor inmate engagement, low-quality facilities, and a lack of trained personnel. As a result, the way independence programs are implemented in correctional institutions is not yet ideal. To overcome these challenges, one must use calculated and intelligent moves. Keywords: Development of Independence; Human Rights; Correctional Institutions